Synthesis and characterization of MgO by microwave-assisted thermal oxidation for dye-sensitized solar cells - Nilphai S. (2017)
© 2016 Trans Tech Publications, Switzerland. Magnesium oxide (MgO) nanostructures were synthesized by microwave-assisted thermal oxidation at various amount of activated carbon additive. The MgO nanostructures were characterized by scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X-ray diffractrometry (XRD) and UV-Visible spectroscopy, respectivly. It was observed that, the obtained MgO have nanocube shape. The MgO nanostructures were applied as a blocking layer in ZnO dye-sensitized solar cells (DSSCs). The photovoltage, photocurrent, and power conversion efficiency characteristics of DSSCs were measured under illumination of simulated sunlight obtained from a solar simulator with the radiant power of 100 mW/cm 2 . The DSSCs with MgO layer exhibited higher current density, open circuit voltage and photoconversion efficiency than those without MgO layer The optimum power conversion efficiency (PCE) was 2.49 % with short circuit current density (J sc ) of 6.61 mA/cm 2 , the open circuit voltage (V oc ) of 0.66 V and the fill factor (FF) of 0.59, respectively.